Comparative study on Post Tonsillectomy use of Antibiotics and Placebo (Bangladesh Journal of Otorhinolaryngology, 2020)
Tonsillectomy is the most frequently performed surgical procedure in Otolaryngological practice. We included 110 patients and divided into antibiotic group and placebo group, and followed up upto 7th POD. Parameters of observation were pain, fever, nausea & vomiting, reactionary & secondary haemorrhage, duration of hospital stay and return to normal diet. The result of this study showed that post operative pain and return to normal diet improved in antibiotic treated group than those who received placebo, but there is no statistically significant difference between two groups in respect of fever, nausea & vomiting, reactionary & secondary haemorrhage and duration of hospital stay.Bangladesh J Otorhinolaryngol; October 2017; 23(2): 153-158